Biology, controls and models of tree volatile organic compound emissions - Monson, Russell K.; Niinemets, Ulo (Tree Physiology, 2013)
The book deals with a highly relevant interdisciplinary topic: tree-atmosphere interactions. Plant-driven volatile organic compound (BVOC) emissions play a major role in atmospheric chemistry, including ozone and photochemical smog formation in the troposphere, and they extend the atmospheric lifetime of the key greenhouse gas, methane. Furthermore, condensation of photo-oxidation products of BVOCs leads to formation of secondary organic aerosols with profound implications for the earth's solar radiation budget and climate. Trees represent the plant life form that most contributes to BVOC emissions, which gives global forests a unique role in regulating atmospheric chemistry. This book, written by leading experts in the field, focuses on recent advancements in understanding the controls on plant-driven BVOC emissions, including efforts to quantitatively predict emissions using computer models. Particular emphasis is on elicitation of emissions under biotic and abiotic stresses, molecular mechanisms of volatile synthesis and emission and the role of emissions in plant stress tolerance. Potentials and limitations of genetic engineering of volatile emissions are also covered. This book addresses all biological scales of organization from molecules to globe and makes a major leap in summarizing and synthesizing the existing information. The main goal of the book is to provide state-of-the-art summary of the exciting field of tree volatile emissions and offer a perspective for future investigations. The book is intended to serve as an invaluable resource for graduate students starting a thesis project on tree volatile emissions as well as serves as a contemporary source of reference for teachers, scientists and professional within and outside the exciting field of plant-driven volatile emissions.